2017
DOI: 10.1007/s00128-017-2134-2
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Based Aquatic Algaecide Adsorption and Accumulation Kinetics: Influence of Exposure Concentration and Duration for Controlling the Cyanobacterium Lyngbya wollei

Abstract: Filamentous mat-forming cyanobacteria are increasingly impairing uses of freshwater resources. To effectively manage, a better understanding of control measures is needed. Copper (Cu)-based algaecide formulations are often applied to reactively control nuisance cyanobacterial blooms. This laboratory research assessed typical field exposure scenarios for the ability of Cu to partition to, and accumulate in Lyngbya wollei. Exposure factors (Cu concentration × duration) of 4, 8, 16, 24, 32 h were tested across th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Copper sulfate has a sorption and depuration profile that is expected to rapidly move to the algae but not effectively internalize for algaecidal effects (Bishop 2016). The sorption kinetics observed by Bishop et al (2017) in short exposures indicate Captain XTR to have increased ability to penetrate into nuisance algae and achieve internal control thresholds, and are not solely driven by active transport from externally sorbed copper. Interactivity of copper from copper sulfate with water chemistry (e.g., alkalinity; Meyer 1999) and algal cells (Crist et al 1990) is predicted to rapidly remove copper mass.…”
Section: Copper Dissipationmentioning
confidence: 94%
See 2 more Smart Citations
“…Copper sulfate has a sorption and depuration profile that is expected to rapidly move to the algae but not effectively internalize for algaecidal effects (Bishop 2016). The sorption kinetics observed by Bishop et al (2017) in short exposures indicate Captain XTR to have increased ability to penetrate into nuisance algae and achieve internal control thresholds, and are not solely driven by active transport from externally sorbed copper. Interactivity of copper from copper sulfate with water chemistry (e.g., alkalinity; Meyer 1999) and algal cells (Crist et al 1990) is predicted to rapidly remove copper mass.…”
Section: Copper Dissipationmentioning
confidence: 94%
“…Surfactants and adjuvants further can increase this interaction with the algal cell and assist in internal transfer (Closson and Paul 2014;Ullah et al 2015). Bishop et al (2017) found pulsed exposures (1-4 h) of Captain XTR can be effective at controlling a nuisance mat-forming algae, although require a proportional increase in concentration at lower durations (i.e., exposure factor). Chelated copper provides more rapid copper internalization than copper sulfate and should be highly considered in short duration exposures such as through canal systems (Bishop 2016).…”
Section: Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Field research with Program 5 in 2013 also supported its effectiveness in applied management programs in these reservoirs . Rapid copper sorption has been documented following Captain XTR exposures, including with short contact times (Bishop et al 2017;Willis et al 2018). The formulation also results in increased internalized copper into L. wollei biomass which is significantly correlated with control (Bishop et al 2018a) and less likely to desorb back into the water (Bishop et al 2018b).…”
Section: Risk Assessment Of Programsmentioning
confidence: 97%
“…Copper products act on algae by decreasing electron transport in photosystem I, preventing cell division, and inhibiting the enzyme catalase (Stauber & Florence, 1987). Several studies have shown that copper‐based algaecides are successful for the control of benthic algae (Bishop, Lynch, Willis, & Cope, 2017; Bishop, Willis, & Horton, 2015; Calomeni et al, 2018). However, the efficacy of these algaecides depends on several factors, such as the formulation of copper used, initial thickness of the benthic algal mat, overall water quality, and the species composing the mat (Bishop, Richardson, & Willis, 2018; Willis, Pearce, & Bishop, 2018).…”
Section: Mitigationmentioning
confidence: 99%